ĐẶC ĐIỂM SINH HỌC CỦA BIẾN CHỦNG Streptomyces orientalis 4912-81-61 SINH VANCOMYCIN - Chu, Thanh Bình; Lê, Gia Hy; Nguyễn, Phương Nhuệ (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
BIOLOGICAL CHARACTERISTICS OF MUTANT STRAIN Streptomyces orientalis 4912-81-61 PRODUCING VANCOMYCIN Vancomycin, which is produced by Streptomyces orientalis, is an antibiotic used in clinical treatment against pathogens resistant to many popular antibacterial agents. The mutant strain Streptomyces orientalis 4912-81-61 producing high yeild of vancomycin was obtained as the result of N-methyl-N’-nitro-N-nitrosoguanidine treatment on the protoplasts of original strain S. orientalis 4912. In the present work, the mutant strain Streptomyces orientalis 4912-81 61 was studied with respect to the biological characteristics. Antibiotic production of this mutant strain was enhanced by 94,3% compared to the original strain. The antibiotic produced by this mutant strain was determined as vancomycin with a anti-microbial spectrum, inhibiting tested strains of genera Bacillus, Staphylococcus and Escherichia. This mutant strain grow at favourable conditions such as pH range of 6-8, temperature of 28-30oC, in medium containing NaCl concentration not more than 6%. The strain S. orientalis 4912-81-61 express enzyme activities to degrade casein, gelatin and starch. The fermentation process producing vancomycin by the mutant strain S. orientalis 4912- 81-61 should be performed more convenient as its abilities of enzyme productivity and utilization of different sugars.